Determinan Pengangguran Terdidik Lulusan Universitas di Pulau Jawa - Leni Anjarwati; Whinarko Juliprijanto (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2021)
This study aims to determine the factors that influence educated unemployment in Java. The data used in this study is secondary data using quantitative methods. Data analysis uses panel data analysis which is a combination of time series and cross-section data. The time-series data uses data for the 2015-2019 period and cross-section data from 6 provinces on the island of Java. The results showed that simultaneously all variables had a significant effect on the level of educated unemployment. While partially shows that the variable level of education and PMDN have a significant positive impact on educated unemployment, and the UMR variable has a significant negative impact on educated unemployment.